PENGARUH KEPERCAYAAN, E-SERVICE QUALITY, DAN INFORMATION QUALITY TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Rizki Gagah Saputra; Adi Santoso; La Ode Sugianto (Gapenas Publisher, 2022)
Marketing management is the science of selecting target markets and reaching, and retaining them by creating, and delivering superior customer value, thereby creating purchasing decisions for consumers. The purpose of this study is to determine the effect of trust, E-Service Quality, and Information Quality on Online Purchase Decisions (Study of Tokopedia Application Users in Ponorogo). The sample is the consumer of the Tokopedia application in Ponorogo who makes a purchase using accidental sampling technique and a sample of 75 respondents. The analysis used in this study uses multiple linear regression analysis using the SPSS 22 program. This study resulted in a partial test (t) as follows: trust (X1) = 0.044, e-service quality (X2) = 0.000, and information quality (X3 ) = 0.002